Модель визначення ризиковості діяльності бюджетних установ - Діденко, Є. В. (ХНУРЭ, 2014)
Risk-taking of functioning of budgetary organizations is an actual state problem. Models of risk-taking are instruments of its permission. In work approach to the solution of a problem of a choice of the organizations with signs of the risks which are subject to control is offered.
Keywords: бюджетна установа; визначення ризиковості діяльності